Rekomendasi Sustainable Business Process menggunakan Prinsip Lean Management (Studi Kasus: Kafe Lokal Kota Malang) - Anatasha Eka Syavina; Intan Sartika Eris Maghfiroh; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Waste is an object that comes from the remaining waste of a product that is no longer used. The increase in waste generation in Indonesia has reached 28 million tons/year. This happens because to lack of awareness many people about the issue of environmental pollution. In addition, there has been an increasing activity of hanging out in cafes that do not implement the concept of eco-friendly. Therefore, the cafe should implement a sustainable business process in the sustainability of a business in order to survive and compete in the long term. The purpose of this research is to fix the problems and improve the quality of business processes with BPMN (Business Process Management Notation) modeling. This research aim to fix problems in business processes. In this research are used lean management because. This method focuses on the value of product and can minimize waste. At the define stage using SIPOC (Supplier, Input, Process, Output, Customer) diagram and waste identification. At the measure stage is identification CTQ (Critical To Quality) and measuring process capability using values of DPMO (Defect Per Million Opportunities). At the analysis stage, this research used Root Cause Analysis (RCA) and BPMN modeling with Bizagi Modeler. From the results of the analysis, it was found that there were four processes that were problematic and identified as wasteful. There is types of waste that occurs in business process is waste inventory, overprocessing, defects and motion. Then improvements business process can minimize waste by changing and adding business process activities.